A novel composite-layered coating enabling self-enhancing thermal barrier performance. (1st April 2019) - Li, Guang-Rong; Wang, Li-Shuang; Yang, Guan-Jun
Abstract: A novel composite-layered thermal barrier coating is designed to solve performance degradation caused by inevitable thermal exposure. Inspired by cathodic protection with a sacrificial anode, a degradation-resistant thermal barrier was achieved by the spontaneous formation of mesopores. The increment of thermal conductivity decreased from 110% for conventional coatings to 40% for composite coatings, which means 50% self-enhanced thermal insulation was realized. A new mechanism based on effective thermal-resistance was proposed to account for the self-enhanced behavior. The effective area for heat flux prevention was increased from 10 to 30% for 2D micropores to 60% for the newly-formed 2D mesopores. Graphical abstract: Unlabelled Image